Written Article Analysis Template (WAAT) for effective critical analysis writing / Roslina Abdul Aziz ... [et al.] - Abdul Aziz, Roslina; Syed Ahmad, Tuan Sarifah Aini; Baharum, Norzie Diana; Awang, Suryani (2022)
Past studies have shown that many tertiary students lack critical thinking skills. Therefore, they face difficulty in analysing and interpreting reading texts and responding critically through writing. Unfortunately, at the tertiary level, critical thinking skills and the ability to write critically and analytically are vital to ensure successful academic endavour. To address the issue, the Written Article Analysis Template (WAAT) was developed to help students to complete their written article analysis assignment for the English for Critical Academic Reading (ELC501) course offered to degree students at Universiti Teknologi MARA (UiTM), Malaysia. The template was developed in early 2020 and implemented in the March-August 2022 semester. A questionnaire based on the Technology Acceptance Model (TAM) was developed and distributed to 138 students who enrolled in ELC501 course at UiTM Pahang, Negeri Sembilan and Kelantan branches. The results show that WAAT was useful in helping students to complete their written analysis assignment since the template comes with complete step-by-step instructions and guidelines which can be easily understood by the students. The students also indicated their intention to use the template in the future and would recommend it to their friends, hence, showing that they were in favour of the WAAT.